PERSEPSI MASYARAKAT TERHADAP BAGI HASIL BANK SYARIAH (STUDI KASUS DI DESA SEDERHANA PERDAGANGAN II) - Allisiya (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
Many people think that profit sharing is the same as conventional bank interest. The purpose of this study was to determine the perception of the Sederhana Village community towards the Islamic bank profit sharing system. This type of research uses a qualitative approach and collects data from the people of Sederhana village by using library materials (library survey). Data collection methods are observation and interview. The data analysis method is by reducing the data and presenting the data to draw conclusions. The knowledge of the Sederhana village community regarding benefit sharing is still relatively low. This is because, in addition to never having been an Islamic bank customer, this community also admits the lack of information and socialization related to this profit sharing. This lack of understanding is one of the factors that influence the perception of most people in Sederhana Village, so they still assume or suspect that profit sharing and conventional bank interest are not much different in the use of Islamic banking services and services.